The Role of Power Inequality in Gender Relations as a Factor Causing Domestic Violence - Erfandi Hasan; Nur Alim; Kurniati (PT. Nawa Edukasi Nusantara, 2026)
Domestic violence (DV) is a form of human rights violation that continues to occur frequently in various levels of society. One of the factors underlying domestic violence is the power imbalance between men and women in domestic relationships. From an Islamic legal perspective, the relationship between husband and wife should be based on the principles of equality, compassion, and justice. However, patriarchal culture often places men in a dominant position, creating an imbalance of power and opening up opportunities for violence. This article aims to analyze the influence of power imbalance in gender relations on domestic violence and to seek solutions to reduce this inequality in accordance with Islamic values.